Impact of EGFR mutation on outcomes following SRS for brain metastases in non-small cell lung cancer. (May 2021) - Moraes, Fabio Y.; Mansouri, Alireza; Dasgupta, Archya; Ramotar, Matthew; Kosyak, Natalya; Weiss, Jessica; Laperriere, Normand; Millar, Barbara-Ann; Berlin, Alejandro; Conrad, Tatiana; van Prooijen, Monique; Heaton, Robert; et al.
Abstract: Introduction: Patients with EGFR -mutated (EGFRm) non-small cell lung cancer (NSCLC) are at particularly high risk of developing brain metastases (BrM). In addition to EGFR targeting tyrosine kinase inhibitors (TKI), radiosurgery (SRS) has an important role in the management of EGFRm BrM. However, data specific to the response and toxicity of EGFRm BrM to SRS are sparse. We evaluated the incidence of local failure (LF) and toxicity of EGFRm and EGFR-wild-type (EGFRwt) BrM treated with SRS. Methods: We analyzed a prospective registry of BrM patients treated at our centre between 2008 and 2017 and identified EGFRm and EGFRwt NSCLC patients treated with SRS ± systemic therapy for BrM. Incidences of local failure (LF) and radionecrosis (RN) were determined, and Cox regression was performed for univariate and multivariate analyses (MVAs). Results: We analyzed data from 218 patients (615 lesions - 225 EGFRm and 390 EGFRwt). Median imaging follow-up per patient was 14.5 months (0.5–96.3). Prior to or concomitant with SRS, 62 % of EGFRm patients received TKI and 93 % received TKI post SRS. The 24-month incidence of LF was 6% and 16 % for EGFRm BrM and EGFRwt, respectively (0.43(0.19−0.95); p = 0.037). The 24-month incidence of RN was 4% and 6% for EGFRm and EGFRwt BrM, respectively (0.8(0.32−1.98) p = 0.63). On MVA, BrM size and prescription dose (PD) significantly correlated with a higher risk of LF and BrM size correlated with a higher risk of RN. Conclusion: We observed excellent rates of response and toxicity following SRS in EGFRm compared to EGFRwt NSCLC, suggesting that EGFRm BrM have a favourable risk benefit ratio compared to EGFRwt NSCLC.